Study of the Mu'jam Al-Kabir Manuscript by Ath-Thabrani Analysis of the Takhrij Hadith on the Prohibition of Wearing Silk Cloth - Rubie Hazinoto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islam is the most perfect religion in the eyes of Allah SWT, because all human actions and behavior have rules and guidelines that must be obeyed and followed so as not to go astray and fall into bad behavior and be hated by the Creator. One of them is dressing, where the etiquette of dressing must cover the private parts completely. In these clothes, there are several restrictions regarding the fabric material. It is forbidden for silk fabric to be used as clothing material, as Rasulullah SAW told us. In this article, the researcher discusses the above hadith taken from one of the hadith scholars, namely Al-Tabrani, in the book A/-Majam Al-Kabir. Al-Tabrani is a hadith expert who was born in Sham in 260 AH/873 AD-360 AH/971 AD, with an age of approximately 100 years. Due to the large number of narrators who narrated a single hadith, this research was conducted with the aim of finding out the authenticity of the hadith and the quality of the content contained in the hadith. So that scholars can get a strong source that can be used as a reference for implementing a law. Literature study (library research) is the method used to support this research. The results obtained from the analysis of this hadith are that the validity of the hadith regarding the prohibition of wearing silk cloth (especially for men) can be proven. Apart from that, the narrator who narrated this hadith can be trusted according to the Rijal al-Hadith scholars. Therefore, the hadith prohibiting men from wearing silk can be used as a haiab.